2018
DOI: 10.1590/0037-8682-0464-2017
|View full text |Cite
|
Sign up to set email alerts
|

Favorable responses to treatment with 5 mg Sbv/kg/day meglumine antimoniate in patients with American tegumentary leishmaniasis acquired in different Brazilian regions

Abstract: Introduction: Favorable responses in American tegumentary leishmaniasis (ATL) patients to treatment with 5 mg Sb v /kg/day meglumine antimoniate (MA) has been reported in Rio de Janeiro, but little is known regarding the therapeutic response to low doses in patients from other locations. Methods: A retrospective review of medical records was conducted to compare the therapeutic response to 5 mg Sb v /kg/day MA treatment among 36 patients who acquired ATL in Brazilian states other than Rio de Janeiro (OS group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…Ensaios, v. 24, n. 3, p. 234-241, 2020 cutaneous and mucosal leishmaniasis, respectively. Although antimonials display important limitations such as high cost (EID RODRÍGUEZ et al, 2019), toxicity and long periods of treatment, the pentavalent antimonial has a clinical cure rate of up to 80% when used in tegumentary leishmaniasis treatment (CATALDO et al, 2018;WHO;PAHO, 2019), similar cure rate was observed in the present study.…”
Section: Characteristics Of Patients In Treatmentsupporting
confidence: 84%
See 1 more Smart Citation
“…Ensaios, v. 24, n. 3, p. 234-241, 2020 cutaneous and mucosal leishmaniasis, respectively. Although antimonials display important limitations such as high cost (EID RODRÍGUEZ et al, 2019), toxicity and long periods of treatment, the pentavalent antimonial has a clinical cure rate of up to 80% when used in tegumentary leishmaniasis treatment (CATALDO et al, 2018;WHO;PAHO, 2019), similar cure rate was observed in the present study.…”
Section: Characteristics Of Patients In Treatmentsupporting
confidence: 84%
“…The pentavalent antimonial has a clinical cure rate of up to 80% when used in tegumentary leishmaniasis treatment (SAHEKI et al, 2017;CATALDO et al, 2018), however this drug display important limitations such as parenteral administration, high toxicity, high cost and long periods of treatment (MARQUES et al, 2019). Antimony therapy is often accompanied by severe side effects that include cardiotoxicity, pancreatitis and hepatotoxicity (SADEGHIAN;ZIAEI;SADEGHI, 2008;LYRA et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, serine proteases activity and differential transcripts expression suggested that each isolate may have independent means to adapt to their niches and that in vitro response to antimony needs further characterization, especially in clinical isolates causing ATL. Laboratory (LaPClinVigiLeish) at INI -Fiocruz were responsible for this classi cation following the criteria reported for ATL patient's treatment in the state of Rio de Janeiro -Brazil (4,5,54). All the isolates included in this study were previously characterized as L. (V.) braziliensis by multilocus enzyme electrophoresis (MLEE), according to procedures described elsewhere (55).…”
Section: Discussionmentioning
confidence: 99%
“…A pentavalent antimony formulation -Glucantime® (Sb V ) -is the rst-line treatment against ATL and has not changed in the last 70 years (1). In South America, this treatment doses (low and high dose) vary according to therapeutic response patterns seen in speci c geographical areas (3)(4)(5). Its mechanism of action is still not completely understood, but, it has been well accepted the hypothesis that Sb V needs to be reduced to its trivalent form (Sb III ), either directly by the parasite or within the host macrophages, to excel leishmanicidal activity (6)(7)(8).…”
Section: Tegumentary Leishmaniasis (Atl) (1)mentioning
confidence: 99%
“…(V . ) guyanensis infections are common, which has poor response to antimonials and should be initially treated with pentamidine [51,52].…”
Section: Discussionmentioning
confidence: 99%